Methamphetamine addiction : biological foundations, psychological factors, and social consequences - Halkitis, Perry N. (American Psychological Association, 2009)
"This book explores methamphetamine from a holistic perspective. It is a literary exploration that encompasses, as the title suggests, biological, psychological, and sociological perspectives. The examination of methamphetamine is expansive, from the development of the substance to the way methamphetamine is depicted in contemporary popular culture. Furthermore, one of the uniquely important aspects of the text is its inclusive examination of the varying methamphetamine-using population. In this sense, the individual user is considered with as much attention as the general trends that influence one person's use. For example, when addressing the "synergetic" relationship between methamphetamine use, mental health, and sexuality, which often leads to high-risk sexual behaviors among MSM, this complex subject is addressed from both the macroperspective as well as the microperspective. Methamphetamine is used with in a cultural context and cannot be thoroughly understood devoid of the relevant cultural constructs and psychological and physiological responses. However, a thorough understanding does not stop at this level, and thus the individual user as well as differences among users is noted. In addition, in stark contradiction to the assertions of some colleagues, while the book explains the highly addictive properties of methamphetamine the author never assumes that every user of the drug is addicted. To explore the depth and range of issues regarding methamphetamine, the author takes his reader on a journey. This volume examines the history of methamphetamine use, as as current trends, while contrasting different drugs and different drug-using populations. The reader learns of the pharmacological properties of methamphetamine and consequently the effects on a user's body and mind, physical, and mental health. Methamphetamine use, abuse, dependence, and addiction are understood as multilayered, as are the current treatment approaches. This volume offers the opportunity to investigate and gain in-depth knowledge of methamphetamine and the individuals who use the drug. Given that the book addresses methamphetamine from different directions, the reader comes to understand methamphetamine from several perspectives. As the totality of the drug is considered, the totality of the drug user is also considered. In reading this volume, one comes to understand the toll methamphetamine takes on the individual body, mind, and soul as well as the effects on a society and public health"--Foreword. (PsycINFO Database Record (c) 2009 APA, all rights reserved).